Thermal and hydrodynamic analysis of MHD nanofluid flow over a permeable stretching surface in porous media: Comparative study of Fe3O4, Cu, and Ag nanofluids - Mahmmoud M. Syam; Mohammad Alkhedher; Muhammed I. Syam (International Journal of Thermofluids)
This study investigates the dynamics of Fe3O4–water, Cu–water, and Ag–water nanofluids in the context of steady, two-dimensional, incompressible laminar magnetohydrodynamic (MHD) boundary layer flow, incorporating the effects of Forchheimer number, thermal radiation, Eckert number, magnetic field parameter, non-dimensional heat generation, and solid volume fraction of nanoparticles. A Newtonian mathematical model is developed, assuming homogeneous nanoparticle distribution, negligible Brownian motion, and thermophoresis effects. Using the operational matrix method (OMM), the model is solved numerically, and the accuracy is validated through L2-truncation errors and boundary condition comparisons. Key findings reveal that increasing the Forchheimer number reduces velocity by up to 4.7% due to enhanced porous drag, while thermal radiation increases temperature by approximately 3.8%, enhancing heat transfer. Higher Eckert numbers elevate temperature by 5.6% due to viscous dissipation, and increasing the solid volume fraction of nanoparticles improves heat transfer efficiency by up to 9.3%. Additionally, the magnetic field suppresses velocity by up to 5.6%, indicating its potential for flow control. These results offer valuable insights into optimizing heat and mass transfer in nanofluid systems under varied thermal and physical conditions.